Structure-function relationship of new crotamine isoform from the Crotalus durissus cascavella - Toyama, D. O.; Boschero, A. C.; Martins, M. A.; Fonteles, M. C.; Monteiro, H. S.; Toyama, M. H. (Springer, 2005)
In this work we isolated a novel crotamine like protein from the Crotalus durissus cascavella venom by combination of molecular exclusion and analytical reverse phase HPLC. Its primary structure was:YKRCHKKGGHCFPKEKICLPPSSDLGKMDCRWKRK-CCKKGS GK. This protein showed a molecular mass of 4892.89 da that was determined by Matrix Assisted Laser Desorption Ionization Time-of-flight (MALDI-TOF) mass spectrometry. The approximately pI value of this protein was determined in 9.9 by two-dimensional electrophoresis. This crotamine-like protein isolated here and that named as Cro 2 produced skeletal muscle spasm and spastic paralysis in mice similarly to other crotamines like proteins. Cro 2 did not modify the insulin secretion at low glucose concentration (2.8 and 5.6 mM), but at high glucose concentration (16.7 mM) we observed an insulin secretion increasing of 2.7-3.0-fold than to control. The Na+ channel antagonist tetrodoxin (6 mM) decreased glucose and Cro 2-induced insulin secretion. These results suggested that Na+ channel are involved in the insulin secretion. In this article, we also purified some peptide fragment from the treatment of reduced and carboxymethylated Cro 2 (RC-Cro 2) with cyanogen bromide and protease V8 from Staphylococcus aureus. The isolated pancreatic beta-cells were then treated with peptides only at high glucose concentration (16.7 mM), in this condition only two peptides induced insulin secretion. The amino acid sequence homology analysis of the whole crotamine as well as the biologically-active peptide allowed determining the consensus region of the biologically-active crotamine responsible for insulin secretion was KGGHCFPKE and DCRWKWKCCKKGSG.
Keywords: crotalus; crotamine; insulin secretion; pancreatic beta-cells; small basic myotoxin